Effectiveness of Using AI Perplexity in Designing Science Learning Materials - Abidah Khoirunnisa Nur; Mukharomah Umi; Febriana Dhista Sela (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The rapid development of Artificial Intelligence (AI) has opened new opportunities for teachers in designing instructional materials. This study aims to describe the effectiveness of using Perplexity AI in designing Natural and Social Science Knowledge (IPAS) materials in elementary schools. Using a quantitative descriptive approach, data was collected through questionnaires from three elementary school teachers as a preliminary study (pilot study). The indicators measured included ease of use, time efficiency, material quality, and usefulness. The research results indicate that Perplexity AI is highly effective, with an overall average score of 4.29, falling into the